Digital language learning and teaching : critical and primary sources. - Thomas, Michael, 1969-; Peterson, Mark, 1965- (London : Bloomsbury Academic, an imprint of Bloomsbury Publishing, 2017)
Digital Language Learning and Teaching: Critical and Primary Sources' offers the most up-to-date information on a field vital to the full understanding of language acquisition and language teaching in the modern era. The four volumes focus on: 'Theories and Frameworks'; 'Focus on the Learner'; 'Teaching with Computer Assisted Language Learning'; 'New Developments in Computer Assisted Language Learning'.
Volume 1. Theory and methodology in CALL / edited by Michael Thomas -- volume 2. Learner perspectives on CALL / edited by Julie Sykes -- volume 3. Teaching with CALL / edited by Hayo Reinders -- volume 4. New developments in CALL / edited by Mark Peterson.
CALL means computer-assisted language learning.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Computer-assisted instruction for foreign speakers; English language -- Study and teaching -- Computer-assisted instruction